THE INFLUENCE OF ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF EDUCATION EMPLOYEES AS MEDIATED BY JOB SATISFACTION (Survey at the Private University of Sleman Regency in Yogyakarta) - Laras, Titi; Jatmiko, Bambang; Tri Nugroho, Fransiskus Joki Hartono (KINERJA, 2021)
UU No. 12 of 2012 concerning Higher Education, discusses universities that are formed and managed on a non-profit basis, called private universities. The difference between public and private, only the founders and managers, for the form of both are similar. Private Universities need competent human resources to manage themThis type of research is quantitative research. The population of this study was employees at a private university in Sleman Regency, Yogyakarta. The sampling technique that will be used is the proportional stratified random sampling method with a total sample of 130 people. The analysis used is Structural Equation Modeling (SEM) analysis.Based on the results of data analysis, the following conclusions are obtained: (1) Organizational Citizenship Behavior (OCB) has a positive effect on Employee Job Satisfaction; (2) Organizational Culture has a positive effect on Employee Job Satisfaction; (3) Organizational Citizenship Behavior (OCB) has a positive effect on the Performance of Educational Employees of Private Universities in Sleman Regency, Yogyakarta; 4) Organizational Culture has a positive effect on Employee Performance; (5) Job satisfaction has a positive effect on employee performance; (6) Job satisfaction is not able to mediate the effect of the variable Organizational Citizenship Behavior (OCB) on the Performance of Educational Employees at Private Universities in Sleman Regency, Yogyakarta; and (7) job satisfaction is not able to mediate the influence of organizational culture on employee performanceÂ Keywords: Organizational Citizenship Behavior (OCB), Organizational Culture, Job Satisfaction, Employee Performance